2020
DOI: 10.7146/hjlcb.v60i0.121312
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Translators through Entrepreneurship in Simulated Translation Bureaus

Abstract: This paper reviews entrepreneurial activities that take place within the simulated translation bureaus of member institutions of the INSTB network and establishes a link between entrepreneurism, self-efficacy and perceived competence. Reusing pre-test and post-test data of a student survey, a first attempt is made to design and test a survey instrument for gauging the impact of a simulated translation bureau on perceived entrepreneurial competence and self-efficacy for planning, setting up, and managin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…On a practical level, it means that translation coursework needs to entail a range of student-centred tasks, conducive to autonomous learning, which involve students either in practice, whereby they engage in simulated professional practice -for example, through student translation bureaus (van Egdom, 2020;Paradowska, 2021;Pietrzak and Kornacki, 2021) and translation projects (Kerremans and van Egdom, 2018) -or in internships, where they gain hands-on professional experience (cf. Elia Exchange, 2014;GALA, 2017;2019).…”
Section: Major Goals Of Contemporary Translator Education and Relevan...mentioning
confidence: 99%
“…On a practical level, it means that translation coursework needs to entail a range of student-centred tasks, conducive to autonomous learning, which involve students either in practice, whereby they engage in simulated professional practice -for example, through student translation bureaus (van Egdom, 2020;Paradowska, 2021;Pietrzak and Kornacki, 2021) and translation projects (Kerremans and van Egdom, 2018) -or in internships, where they gain hands-on professional experience (cf. Elia Exchange, 2014;GALA, 2017;2019).…”
Section: Major Goals Of Contemporary Translator Education and Relevan...mentioning
confidence: 99%
“…These studies generally confirmed the growing curriculum–industry gap and advocated for pedagogical modification. In response, other scholars delved into designing instructional activities underlying authentic experiential learning, for instance, simulations (Li, 2015 ; Kiraly and Massey, 2016 ; Van Egdom et al, 2020 ), team-based learning (Massey and Braendli, 2016 ), projects (Peverati, 2013 ; Santafé, 2014 ; Thelen, 2014 ), internships (Astley and Torres-Hostench, 2017 ; Li, 2018b ), or mentorships (Olalla-Soler, 2018 ). Meanwhile, another important direction of scholarly research on this front has been concerned with market exploration, such as user expectation surveys (Pöchhacker, 1994 ; Diriker, 2011 ) or job ad analysis (Wang and Li, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the translation market, characterized by Dunne (2012) as industrialization of translation, create incentives to widen the scope of translator education to include a variety of translation-related tasks like project management and quality assurance (Biel 2011). Collaborative translation company simulations (see, for example, van Egdom et al 2020;Konttinen et al 2017) where students set up and run their own translation companies have emerged as a promising method for preparing translation students for successful careers in the translation industry.…”
Section: Introductionmentioning
confidence: 99%